ADVANCE research 20 years later - Zh. D. Kobalava; E. L. Kolesnik (Евразийский Кардиологический Журнал)
Observational and interventional studies have shown that intensive blood pressure control may benefit in patients with diabetes. The Action in Diabetes and Vascular Disease: Preterax and Diarnicron MR Controlled Evaluation (ADVANCE) international randomized, controlled, clinical trial was launched in 2001. According to the results of the study, the risk of major micro- and macrovascular events (primary endpoint) significantly decreased by 9%, while the risks of cardiovascular death and death from any cause decreased by 18% and 14%, respectively. There was a decrease in the risks of microvascular complications – any renal event, the appearance or worsening of nephropathy and the appearance of microalbuminuria by 21%, 18% and 21%, respectively. The results of the antihypertensive part of the ADVANCE study supplemented the expanding evidence base and served as the basis for changing clinical guidelines for the management of patients with hypertension and diabetes. According to the updated joint guidelines of the European Society of Cardiology / European Association for the Study of Diabetes (ESC/EASD), the target systolic / diastolic blood pressure levels should be 130/80 mmHg, with some exceptions, and the fixed combination of the RAAS blocker with a diuretic or calcium antagonist is suggested as first-line therapy.The observational ADVANCE-ON study, which enrolled 8494 patients out of 11 140 patients randomized to the ADVANCE study, found a memory effect, or ‘inheritance’, in which intensive blood pressure control during the study had a beneficial effect on various outcomes after its termination. These findings highlight the importance of achieving and maintaining optimal blood pressure control to reduce the risk of micro- and macrovascular complications.